Bushman Letters : Interpreting |Xam Narrative - Wessels, Michael (Professor of English) (Book collections on Project MUSE., 2010)
The Bleek and Lloyd Collection consists of the notebooks in which William Bleek and Lucy Lloyd transcribed and translated the narratives, cultural information and personal histories told to them in the 1870's by a number of /Xam informants. It represents a rare and rich record of an indigenous language and culture that no longer exists. The /Xam materials have exerted a fascination for anthropologists and poets alike. They are compromised, mysterious, and yet essential. How does one begin reading texts that are at once so compromised and so unique? Bushman Letters: Interpreting /Xam Narrative.